Some Indications Of Large Abdominal Fluid In Aseptic Pododematitis In Cows (Eurasian Scientific Herald, 2023)
This article presents an examination of large abdominal fluid pH disorder and large abdominal movement changes in aseptic pododermatitis in cattle hooves of the breed.